LUARAN VISUAL ANTARA VITREKTOMI YANG DILAKUKAN SECARA DINI DAN TERTUNDA PADA PASIEN ENDOFTALMITIS YANG DIOPERASI DI RUMAH SAKIT KARIADI SEMARANG : STUDI DESKRIPTIF SELAMA DUA TAHUN - Rahmayanti, Suci; Pragnanda, Satya Hutama (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2023)
Introduction : Endophthalmitis is a medical emergency caused by infection of tissue or fluids inside the eyeball. Vitrectomy for endophthalmitis is one of the treatment choice and leads to VA gains in some cases. Timing of surgery and visual outcome after surgery are vital to acknowledge. This study aims to analyze the difference of visual outcome between early and delayed vitrectomy in endophthalmitis patients operated in Dr. Kariadi General Hospital Methods : A Retrospective study held from medical record of patients with endophthalmitis underwent vitrectomy surgery from January 2021 – January 2023 in Dr. Kariadi General Hospital, Semarang. Endophthalmitis patients caused by trauma were excluded. All of the patients had immediate vitrectomy, and based on the onset, the patients were divided into two groups, early vitrectomy (onset ? 7 days) and delayed vitrectomy (onset > 7 days). Independent t- test method was used to analyze the data (significant if p<0.05) Result : Totally 30 endophthalmitis patients (30 eyes) were obtained. There were 18 patients (60%) had early vitrectomy and 12 patients (40%) had delayed vitrectomy. Postoperative examination showed 13 (72%) patients with early vitrectomy had improved VA, and 5 (28%) had constant VA. On the other hand, patients with delayed vitrectomy showed 5 (42%) had improved VA, 6 (50%) had constant VA, and 1 (8%) had decreased VA. The difference between two groups was significant (p=0.014) Conclusion : This study found endophthalmitis patients with early vitrectomy had significant better visual outcome than delayed vitrectomy.